Let's go camping - Slade, Suzanne (New York : PowerKids Press, 2007)
An introduction to the sport of camping, discussing trip planning, camping gear, tents, cooking, and camping in all kinds of weather.
Camping -- Planning your camping trip -- Choosing a campsite -- Camping gear -- Pitching a tent -- Camping in all kinds of weather -- Campfire cooking -- Around the campfire -- Camp critters -- Camping and nature -- Let's go camping! -- Safety tips.
Includes index.
5.1
3-6
Keywords: Camping -- Juvenile literature; Camping